Determinants of Sharia Bank Firm Value with Financial Performance as a Moderating Variable - Rupilu, Wilsna; Tanan, Eugenia Hendrini P.; Mudamakian, Agnes Kidi Beda (Public Policy, 2025)
This study examines the impact of Islamic Good Corporate Governance, Islamic Corporate Social Responsibility, Intellectual Capital, and Firm Size on Firm Value. Using a causal quantitative approach, the study analyzed 13 Islamic banking companies registered with the Indonesian Financial Services Authority (OJK) from 2019 to 2023. A purposive sampling technique resulted in a sample of 45 companies. Hypothesis testing was conducted using multiple linear regression and moderated regression analysis (MRA). The findings show that all independent variables influence Firm Value. Additionally, ROA moderates the relationship between Islamic Good Corporate Governance, Islamic Corporate Social Responsibility, and Firm Size with Firm Value but does not moderate the relationship between Intellectual Capital and Firm Value.